ABSENCE OF AN ASSOCIATION BETWEEN OXIDATIVE STRESS AND PREGNANCY OUTCOME FOLLOWING FTAI IN BUFFALO DURING SUMMER AND WINTER SEASON - P. KUMAR, P; PANDEY, AK; PHULIA, SK; KUMAR, S; SHARMA, RK; KUMAR, L; BISHNOI, N (The Indian Journal of Animal Reproduction, 2016)
Thirty-eight cyclic Murrah buffalo in summer (n=20) and winter (n=18) season were subjected to a fixed time artificial insemination (FTAI) protocol. Oxidative stress parameters were assessed on different days of protocol. Season had no impact on pregnancy rate (summer, 25%; winter, 27.8%; p>0.05) following FTAI in buffalo. Lipid peroxidation in terms of malondialdehyde (MDA) concentration was higher during summer as well as on the day of AI in summer as well as in winter season (p<0.05). Glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) activity was similar (p>0.05) between summer and winter season. In brief, oxidative stress parameters had no conclusive association with pregnancy outcome in buffalo during summer season.